Validation of new potential targets for remission and low disease activity in psoriatic arthritis in patients treated with golimumab - Coates, L; Rahman, P; Psaradellis, E; Rampakakis, E; Osborne, B; Lehman, A; Nantel, F (Oxford University Press, 2018)
Objectives Treat to target recommendations for PsA state that the target of treatment should be remission or, at the very least, low disease activity. Different clinical indexes have been proposed to define these disease states including the minimal disease activity criteria and the Disease Activity Index for PsA (DAPSA) scores, which have 7 and 4–5 domains, respectively. Using a Canadian cohort, the objectives were to calculate the proportion of patients achieving these criteria, their prognostic value and the overall patient impact of these disease states. Methods BioTRAC is an ongoing, prospective registry of inflammatory arthritis patients. 188 PsA patients treated with golimumab were included. Data collected at baseline, 6 and 12 months were used. Results Between 15.6% and 38.3% of patients achieved remission, and 37.4–77.7% achieved low disease activity at 6 and 12 months’ follow-up. Patients achieving any minimal disease activity target and DAPSA low disease activity had significantly lower swollen joint count, tender joint count, psoriasis area and severity index, dactylitis and enthesitis scores compared with non-achievers (P ≺ 0.05). Higher HAQ scores (P ≺ 0.03) were observed in patients achieving remission with remaining dactylitis or active skin disease. Conclusion Very low disease activity was the most stringent new potential target for remission in PsA. There was a high level of agreement between scores, although residual activity in dactylitis and skin despite DAPSA remission may affect patient function. Patients achieving either DAPSA endpoint, however, did not show a significant reduction in skin disease, indicating that those two criteria are more restricted to joint symptoms.